Role of cardiac MRI in detecting familial hypertrophic cardiomyopathy : Review / Marymol Koshy … [et al.] - Marymol, Koshy; Johari, Bushra; Hamdan, Mohd Farhan; Hanafiah, Mohammad (Faculty of Medicine, 2016)
Hypertrophic cardiomyopathy (HCM) is a global disease affecting people of various ethnic origins and both genders. HCM is a genetic disorder with a wide range of symptoms, including the catastrophic presentation of sudden cardiac death. Proper diagnosis and treatment of this disorder can relieve symptoms and prolong life. Non-invasive imaging is essential in diagnosing HCM. We present a review to deliberate the potential use of cardiac magnetic resonance (CMR) imaging in HCM assessment and also identify the risk factors entailed with risk stratification of HCM based on Magnetic Resonance Imaging (MRI). KEYWORDS: Hypertrophic cardiomyopathy (HCM), Magnetic Resonance Imaging (MRI), Sudden Cardiac Death (SCD), Late gadolinium enhancement (LGE), Phenotypes, Left ventricular hypertrophy (LVH), Left ventricular outflow obstruction (LVOT), Risk Stratification.